An exploration of context and learning in endurance sports coaching - Kirkland, Andrew; Cowley, Joe (Frontiers in Sports and Active Living, 2023)
This study explored contextual factors relating to coach learning of an international cohort of endurance sports coaches. Following ethical approval, 839 coaches, 612 coached athletes and 8352 non-coached athletes participated in the research. A critical realist research philosophy was adopted, in which self-completion surveys were developed in consultation with coaches and industry end-users. The context was dominated by remote coaching practices and digital technology which shaped how coaches learn and thus, what it meant to be a coach. Unmediated learning sources were biophysically biased and largely delivered through marketised platforms designed to sell products. The study findings have broader implications within sport and education, in which it is suggested that distance learning platforms may create a sense of psycho-emotional detachment in which capacity for learning can be limited.